INTENTIONAL ENGLISH TYPOGRAPHY ERRORS ON FACEBOOK - Sihindun Arumi; Arin Arianti; Veronika Unun Pratiwi; Mas Sulis Setyono (Universitas Veteran Bangun Nusantara, 2019)
This research aims to identify the linguistics unit used in intentional English typography errors, whether in the forms of word, phrase, clause or sentence. This research also has purpose to describe the types of intentional English typography errors, whether in the forms of omission,addition, substitution, or transposition. This research was a kind of qualitative design that tried to describe the linguistic units andforms of intentional English typography errors on facebook. Data of this research were Englishwords containing intentional typography errors used by the researchers’ friends on facebook in writing their status or comments. The data were got from the source of facebook in which data were collected through an observation toward English typography errors on status or commentson friends’ facebook accounts. The data then, were documented through facilities of print screen (capturing by computer) or screenshoot (capturing by phone cellular). Next, the collected data were analyzed into three steps, namely reduction, display, and verification. To check the data validity, this research applied researcher triangulation.This research resulted in collecting 93 data. The linguistic units consisted of 88 words, 1 phrase, and 4 clauses. The words involved 51 nouns, 8 adjectives, 13 verbs, 3 adverbs, and 13 greeting words. Then the linguistic units could be clasified in 65 substitution that can be categorized into 16 letter substitution and 49 sound substitution. There were also data belonging to 5 addition,11 ommission, and 1 transposition. It was also found combined-forms, namely 6 substitution – addition, 3 substitution – ommission, and 2 addition – ommission.